Electronic property modulation in two-dimensional lateral superlattices of monolayer transition metal dichalcogenides. Issue 29 (11th July 2022) - Zou, Hongshuai; Wang, Xinjiang; Zhou, Kun; Li, Yawen; Fu, Yuhao; Zhang, Lijun
Abstract : By using first-principles high-throughput calculations, we explore how the two-dimensional lateral superlattices modulate electronic structures and electronic properties of monolayer transition metal dichalcogenide. Abstract : Fabricating lateral heterostructures (HSs) and superlattices (SLs) provides a unique degree of freedom for modulating the physical properties of two-dimensional (2D) materials by varying the chemical component, geometric size and interface structure in the ultra-thin atomic thickness limit. While a variety of 2D lateral HSs/SLs have been synthesized, especially for transition metal dichalcogenides (TMDs), how such structures affect quantitatively the physical properties of 2D materials has not yet been established. We herein explore electronic property modulation in 2D lateral SLs of monolayer TMDs through first-principles high-throughput calculations. The dependence of the electronic structure, bandgap, carrier effective masses, charge density overlap on chemical components, interface type, and sub-lattice size of lateral TMD-SLs are investigated. We find that by comparison with their random alloy counterparts, the lateral TMD-SLs exhibit generally type-II band alignment, a wider range of bandgap tunability, larger carrier effective masses, and stronger electron–hole charge separation tendency. The bandgap variation with a sub-lattice size shows larger bowing parameters for the SLs with heterogeneous anions, by comparison with the homogeneous anion cases. A similar behavior is observed for the SLs with an armchair-type interface, by comparison with the zigzag-type interface cases. Further analyses reveal that the underlying physical mechanism can be attributed to the synergistic interplay among the band offset of sub-lattices, quantum confinement effect, and existing internal strain.